Evaluation of Gastrointestinal Parasitic Infection Among Primary School Pupils in Lokoja, Kogi State, Nigeria - Saleh, R,; Audu, P.A,; Ngwamah, J. S., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Intestinal parasites are parasites that populate the gastrointestinal tract, they are mainly protozoans and helminthes. The Gastrointestinal parasitic infection was evaluated among primary school children in Lokoja metropolis Kogi State, Nigeria. The study was carried out in twenty (20) randomly selected primary schools. A total of 332 stool samples obtained from primary school age children comprising 182 males and 150 females, aged between 4->12 years were examined microscopically for gastrointestinal parasites. Out of the 332 samples examined, 121 (35.83%) were positive for intestinal parasites. 11 species of the intestinal parasites were encountered. Hookworm infection was the most prevalence (10.84%) followed by Fasciola hepatica (8.70%), Ascaris lumbricoides, and Entamoeba histotolytica with 3.61% each. Strongyloides stercoralis, Taenia saginata, Enterobius vermicularis and Diphyllobotrium latum, has 2.71%, 1.81%, 1.51% and 1.2% respectively. Trichuris trichiura, Balantidium coli and Schistosoma spp recorded the least prevalence with 0.90% each. The result of the study has shown that intestinal parasites were prevalent in the study area, and for this reason, control measures, such as chemotherapy, provision of adequate sanitary facilities, portable drinking water, improved personal hygiene and health education should be the focus of the community, government and non-governmental organizations.